Drinking norms, readiness to change, and gender as moderators of a combined alcohol intervention for first-year college students. (January 2016) - Grossbard, Joel R.; Mastroleo, Nadine R.; Geisner, Irene Markman; Atkins, David; Ray, Anne E.; Kilmer, Jason R.; Mallett, Kimberly; Larimer, Mary E.; Turrisi, Rob
Abstract: Introduction: Alcohol interventions targeting college students and their parents have been shown to be efficacious. Little research has examined moderators of intervention efficacy to help tailor interventions for subgroups of students. Method: This study is a secondary data analysis of readiness to change, drinking norms, and gender as moderators of an efficacious peer- and parent-based intervention (Turrisi et al., 2009). Students (n = 680) were randomized to the combined peer and parent intervention ( n  = 342) or assessment-only control ( n  = 338). Results: The combined intervention reduced peak blood alcohol content (BAC) compared to control. Gender and norms did not moderate the relationship between the intervention and drinking. Significant interactions were found between gender, precontemplation, and intervention. Students in the combined condition with higher precontemplation had lower weekly drinking compared to those with lower precontemplation. This pattern was also found among men for peak BAC and alcohol-related consequences but not among women, indicating a three-way interaction. Conclusion: Interventions may need to consider readiness to change and gender to optimize effectiveness. Highlights: Combining parent and peer interventions shows promise in reducing student drinking. We examine readiness to change, norms, gender as moderators of intervention efficacy. Significant two-way and three-way interactions were found.